Pelatihan Pemanfaatan Media Kartu Huruf Berbasis Audio Visual untuk Meningkatkan Kemampuan Daya Ingat - Hadi Gunawan Sakti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Technological advancements directly influence the field of education, particularly shifting the paradigm of interaction between teachers and students. This influence demands teachers to innovate and create using available technology. Teacher creativity significantly impacts the quality of the learning process. Learning media supports the learning process and holds a crucial position within the educational system. Without media, communication during learning processes becomes less engaging, potentially making learning less appealing and boring. Utilizing audio-visual-based letter card media to enhance student memory skills at the PAUD Al-Ikhtiar, teachers and students can easily utilize these cards during their learning process. This enhances teachers' understanding and ability to use audio-visual letter-based media effectively, creating a more enjoyable learning environment and improving students' memory, thereby enhancing children's interest in reading. The method employed in this community service program includes participatory training in utilizing learning media. The program's execution involves a team approach with university faculty members assigned to assist teachers, ensuring the training's optimal implementation. Implementation methods encompass activity coordination, resource preparation, execution, and evaluation. The results of the community service initiative were met with enthusiasm and motivation among participants. Practically, it can be concluded that 88% of training participants have effectively developed the Linktree learning media.